Some approaches to solving the problems of teaching the disciplines of the natural science cycle and computer science in rural small schools - Anosov Y. V., Razboeva aleksandrova V. I. (Scientific and Educational Areas Under Modern Challenges, 2022)
The article deals with the problems and peculiarities of teaching science and IT in small rural schools. Moreover, it looks upon incomplete classes and forming shared classes filled with student of different levels of education. To underline the importance of the given problem the authors of the article pro-vide the readers with statistics of the percentage of rural schools and of num-ber of students studying there. The article also contains various solutions of the objective problem of teaching science and IT in such schools.
Keywords: информатика; образовательные технологии; technical equipment; Teaching Methods; educational technologies; software; методики преподавания; кадровый дефицит; оснащение программным обеспечением; staff shortage; small rural schools; access to the Internet; малокомплектные сельские школы; оснащение аппаратным обеспечением; доступ к сети Интернет